2015
DOI: 10.1097/xeb.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Is the practice of public or private sector doctors more evidence-based? A qualitative study from Vellore, India

Abstract: Better training in evidence-based practice, improved regulatory system and greater collaboration between the public, private for-profit and private not-for-profit sectors with regards to training in evidence-based practice - literature search and critical appraisal skills - were suggested as needed to improve the present situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…One study from Uttar Pradesh, India, including a diverse mix of community health centres, district hospitals, and medical colleges, reported that quality of routine care for uncomplicated deliveries was generally poor but was better in the private compared with the public sector [27]. Another study indicated that knowledge of evidence-based practices seemed to be insufficient in practitioners from both the private and public sector in India [28].…”
Section: Introductionmentioning
confidence: 99%
“…One study from Uttar Pradesh, India, including a diverse mix of community health centres, district hospitals, and medical colleges, reported that quality of routine care for uncomplicated deliveries was generally poor but was better in the private compared with the public sector [27]. Another study indicated that knowledge of evidence-based practices seemed to be insufficient in practitioners from both the private and public sector in India [28].…”
Section: Introductionmentioning
confidence: 99%